MICROWAVE ABSORPTION IN BARIUM HEXSAFERITE WITH GADOLINIUM DOPING: JOURNAL REVIEW - Septina Yanti, Anisa; Nasution, Nazaruddin; Sirait, Ratni (EINSTEIN (e-Journal), 2026)
This study examines the effect of gadolinium (Gd) doping on barium hexaferrite (BaM) on its magnetic properties and electromagnetic wave absorption capacity. The synthesis methods used include sol-gel, auto-combustion, and solid-state reaction, each of which influences particle size, crystal structure, and magnetic properties of the material. The results show that Gd doping reduces particle size to 180–200 nm, increases coercivity (Hc) to 4800–5000 Oe, and decreases saturation magnetization (Ms), which implies enhanced microwave absorption with a reflection loss (RL) value reaching −40 dB in the X-band. The primary absorption mechanism involves improved impedance matching and magneto-dielectric relaxation. These findings indicate that Gd-doped BaM has great potential as a microwave absorber material for radar stealth and electromagnetic protection applications.